2016
DOI: 10.1007/s11126-016-9417-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Objective and Subjective Life Balance Between Women With and Without a Personality Disorder

Abstract: Life balance is associated to health, well-being and quality of life and is a target of psychiatric rehabilitation interventions. However, little is known about this life dimension in women living with personality disorders. The purpose of this descriptive-correlational study was to compare and explore relationships between subjective life balance, objective time use, quality of life and perceived stress in women without a mental health disorder (n = 43) and women with a personality disorder (clusters B and C)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 36 publications
0
4
0
1
Order By: Relevance
“…Studies have identified that women with a diagnosed personality disorder did not feel competent in carrying out activities, had few organised daily activities and felt their daily routine lacked meaning (Falklöf and Haglund, 2010; Larivière et al., 2016). People with a mood disorder may experience difficulty sleeping or excessive sleeping (Berk, 2009), and people with a diagnosed personality disorder can experience poor sleep quality, which impacts on their ability to participate in occupations (Wood et al., 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies have identified that women with a diagnosed personality disorder did not feel competent in carrying out activities, had few organised daily activities and felt their daily routine lacked meaning (Falklöf and Haglund, 2010; Larivière et al., 2016). People with a mood disorder may experience difficulty sleeping or excessive sleeping (Berk, 2009), and people with a diagnosed personality disorder can experience poor sleep quality, which impacts on their ability to participate in occupations (Wood et al., 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other studies have found that women more often experience imbalance in their daily lives due to high demands at home, resulting in decreased self-care, rest and recovery, which can affect their health [6163]. Another study found that, compared with women without a mental illness, women with personality disorders experienced higher stress, less subjective balance, and were found to value rest less [64]. Thus, in relation to the current study’s findings, it is possible that female mental health service users had more room for improvement in the area of self-care.…”
Section: Discussionmentioning
confidence: 99%
“…(2013), le statut marital, la scolarité, le nombre d’enfants vivant au domicile, le statut d’emploi, le fait de vivre ou non dans un milieu urbain, être propriétaire ou locataire pouvaient influencer la perception de son équilibre de vie. Par ailleurs, plusieurs études font état de relations entre l’équilibre occupationnel et la santé, le bien-être ou la qualité de vie chez différents groupes de personnes, dont des personnes issues de la population générale sans problème de santé incapacitant (Anaby et al, 2010; Larivière et al, 2016; Matuska, 2012b; Wagman et al, 2017), des travailleurs ou des professionnels de la santé (Håkansson et Ahlborg, 2010), des parents (Håkansson et al, 2019; Wada et al, 2010), des personnes vivant avec un trouble de santé mentale (Bejerholm, 2010; Larivière et al, 2016; Leufstadius et al, 2006; Ung et al, 2018), des personnes vivant avec la polyarthrite rhumatoïde (Forhan et Backman, 2010; Wagman et al, 2020), des personnes présentant une obésité ou un autre problème de santé limitant leur degré d’activité physique (Levasseur et Larivière, 2015; Matuska et Bass, 2016), ainsi que les personnes ayant subi un accident vasculaire cérébral (Kassberg et al, 2021).…”
Section: Introductionunclassified